1995
DOI: 10.1136/jmg.32.12.994
|View full text |Cite
|
Sign up to set email alerts
|

Del(3) (p25.3) without phenotypic effect.

Abstract: A terminal deletion of chromosome 3 at p25.3 was observed during prenatal diagnosis. A similar deletion is also present in the phenotypically normal mother. The deletion was confirmed by FISH. The breakpoint is distal to the region responsible for the 3p-syndrome. A normal baby girl was born with no apparant phenotypic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 3 publications
2
53
0
3
Order By: Relevance
“…In fact, a 3p25.3 terminal deletion with no apparent abnormalities has been demonstrated in a mother and her child. 24 Similarly, a characteristic phenotype associated with deletions at 7q36 was not found in a second trimester foetus with an inverted duplication of chromosome 7 in association with a deletion within 7q36. 10 However, the loss of the DEF1 gene in all cases of inverted 8p duplication/deficiencies supports the assumption that during the process of repair of an aberrant recombination, important genes are both duplicated and deleted.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a 3p25.3 terminal deletion with no apparent abnormalities has been demonstrated in a mother and her child. 24 Similarly, a characteristic phenotype associated with deletions at 7q36 was not found in a second trimester foetus with an inverted duplication of chromosome 7 in association with a deletion within 7q36. 10 However, the loss of the DEF1 gene in all cases of inverted 8p duplication/deficiencies supports the assumption that during the process of repair of an aberrant recombination, important genes are both duplicated and deleted.…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore surprising that only a very small number of innocuous autosomal deletions have been reported (deletions of the X chromosome should be considered as a separate group as they can be tolerated in females through selective X-inactivation). These locate to chromosome regions 2p12.2 → p13 (Lambert and Collinson, 1991), 2q13 → q14.1 (Sumption et al, 2001), 3p25.3 (Knight et al, 1995), 5p14 (Hand et al, 2000;Overhauser et al, 1986), 6q22.3 → q24.2 (Kumar et al, 1999), 8p23.1 (Reddy, 1999), 8q24.13 → q24.22 (Batanian et al, 2001), 11p12 (Barber et al, 1991), 13q21 (Couturier et al, 1985) and 16q21 (Hand et al, 2000;Witt et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Remarkably, Knight et al 39 reported a phenotypically normal mother and child both with a terminal 3p25.3 deletion, which suggests that a deletion distal to 3p25.3 does not need to have an apparent deleterious effect.…”
Section: Pmentioning
confidence: 99%